Féminismes et luttes contre l'homophobie: de l'apprentissage à la subversion des codes - Bard, Christine; Bastien Charlebois, Janik; Boisclair, Isabelle; Bourque, Dominique; Charbonneau, Amélie; Deshoulières, Étienne; Horincq Detournay, Rosine; Laprade, Bruno; Lebreton, Christelle; Maiorano, Sabrina; Ricard, Nathalie; Vallerand, Olivier (Les cahiers de l'IREF. Collection Agora, 2016)
En 1903, à Berlin, Anna Rueling appelait le mouvement homosexuel et le mouvement des femmes à s’entraider puisque tous deux luttaient pour la liberté et l’autodétermination individuelle. Plus d’un siècle plus tard, quelles convergences peut-on observer entre féminismes et luttes contre l’homophobie? Sur le plan de la pensée, quels rapprochements contemporains peut-on établir entre le champ des études féministes et celui de la diversité sexuelle et de genre? Comment s’articule l’intersection entre ces deux systèmes de différenciation hiérarchique que sont le sexisme et l’hétérosexisme ? Quels théories et concepts y circulent de manière transversale, et avec quelles redéfinitions? Ces questions ont guidé l’organisation du colloque «Féminismes et luttes contre l’homophobie: zones de convergence» tenu dans le cadre du congrès de l’ACFAS 2014 à l’Université Concordia, Montréal, le 16 mai 2014.
Keywords: amériques; approches et analyses; corps; cours; discipline; droit; empowerment; europe; france; homophobie; lesbianisme; pol5185; politique; pornographie; premier cycle; queer; québec; régions géographiques; science politique; science politique et droit; sciences humaines; sexualité; sociologie; thématiques; violences; violences contre les femmes*; violences sexistes et sexuelles

Beyond Gratification:The Benefits of Pornography and the Demedicalization of Female Sexuality - Jeneanne Orlowski (The Modern American, 2012)
This Paper argues that non-obscene adult pornography should remain protected by the United States Constitution because it has contributed to the demedicalization of female sexuality. There is an ongoing debate among feminists regarding the value of pornography and whether it should be protected under the First Amendment. This Paper explains the background of the debate regarding the status of pornography as a form of speech and whether it has value that warrants its protection. Specifically, this Paper focuses on the removal of nymphomania from the Diagnostic and Statistical Manual and its absence as a modern medical diagnosis as an example of the demedicalization of female sexuality. The demedicalization of female sexuality has positively affected women in the United States. Catalysts for this demedicalization include the production and consumption of adult pornography by women. For this reason, adult pornography deserves continued protection as a form of free speech under the First Amendment.
Keywords: amériques; corps; cours; discipline; droit; droits des femmes*; premier cycle; régions géographiques; santé; science politique et droit; sex1911; sexualité; sofia; thématiques; états-unis

Law Reform, Lesbian Parenting, and the Reflective Claim - Leckey, Robert (Social & Legal Studies, 2011)
The article aims to complicate efforts to make law fit or catch up to social practices. It scrutinizes the ‘reflective claim’ using the case study of recognition of parenting by lesbian couples. Reforms in the United Kingdom’s Human Embryology and Fertilisation Act 2008 and the Canadian province of Quebec’s civil code are compared with empirical work from the social sciences on lesbians’ family practices. The reflective claim rests on problematic ideas about social practices and law. Since law is always blunt and incomplete, choices must be made as to which practices it should aim to recognize. Furthermore, the impact of heterosexist and homophobic conditions on lesbian families means that observable practices may not be a suitable model for gay-affirmative reforms. As advanced in the literature, the reflective claim overlooks law and society’s complex interaction, including how reform will not merely reflect but also alter practices. It fails to do justice to law reform’s normative character, obscuring its costs and positive potential
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; angleterre; approches et analyses; canada; corps; cours; discipline; discours dominant; droit; droit des femmes*; europe; hétérosexisme; identités LGBTQIA2+; inégalités; maternité; parentalité; premier cycle; périodes historiques; queer; québec; régions géographiques; science politique et droit; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques

Decoding Black Women: Policing Practices and Rape Prosecution on the Streets of Philadelphia - Irving, Toni (NWSA Journal, 2008)
Black women are generally displaced as victims of rape. The police response to the sexual assault of black women in general and lower-class black women in particular is illustrative of how sexual ideologies help construct complex social hierarchies that in turn structure rights. How the law currently deals with rape places black women outside of the narrative frames that legitimate entitlement. Rape continues to stand in for, and effectively obscure, other social, political, and economic concerns. Unpublished and often ignored, the rape narrative is a ripe site to supply oppositional interpretations of national experience and transmit some of the structural problems in the criminal justice system. Pulling from over two thousand “real” rape cases of low-income black women ignored and not investigated in Philadelphia between 1995 and 2000, this article reads black female rape narratives as case studies in order to discuss the way personal narratives of rape victims are structured by competing and overwhelming sociolegal narratives that undercut their reception. As the fastest growing prison population, the presence of the law to punish black women stands in stark contrast to the absence of the law to protect them.
Keywords: 1900-1999; 1990-1999; afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; droit; droit des femmes* noires; droits des femmes*; féminisme afroaméricain; histoire et politique; intersectionnalité; inégalités; philadelphie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sex2283; sexisme; systèmes d'oppressions; thématiques; viol; violences; états-unis; études littéraires

L'Envers de la nuit: les femmes contre la pornographie - Lederer, Laura; Audy, Monique; Dufresne, Martin (Collection Les Entêtées, 1983)
Keywords: 1900-1999; amériques; approches et analyses; corps; cours; discipline; droit; féminisme pop; premier cycle; psychologie; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

Pornography, civil rights, and speech. (the 1984 Francis Biddle Memorial Lecture, Harvard Law School, April 5, 1984) (transcript) - MacKinnon, Catharine A. (Harvard Civil Rights-Civil Liberties Law Review)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; corps; cours; discipline; droit; histoire et politique; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; science politique et droit; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis